Partnership with Aqua Consultants – A Pragmatic Approach for an Effective Aquaculture Extension Service - Kumaran, M. (Indian Journal of Extension Education, 2016)
Aquaculture contributes substantially for the socio-economic progress of small scale fish farmers. Aquaculture extension  service is the 'facilitative force'for the farmers to access technical and managerial skills, information on quality inputs and  premium market and mobilizing them for collective compliance of regulatory guidelines and better management  practices. The private extension service providers known as 'aqua-consultants' were found to be the actual extension  workers in aquaculture due to the ineffective multi-constrained public funded extension departments. An inclusive  partnership approach involving these private extension service operators for on-farm research and extension out reach  would rather be beneficial to the system than trying to excluding them. With this understanding a study was conducted  with private extension service providers in two aquaculture dominant states of India to assess their profile characteristics  and operational particulars, identify the criteria for registration of the private extension service provider, identify potential  areas for collaboration and to suggest a strategy and framework to build the partnership with aqua-consultants for an  effective aquaculture extension service. The results indicated that the private extension service providers were technically  qualified professionals, many of them were farmers themselves, had adequate field experience, good hold-on group of  farmers and their perceived success rate was more than 80 per cent. They updated mostly through their own practical  experiences but preferred to have interaction with researchers. Based on this a brainstorming workshop was held with  them wherein the researchers, aqua-consultants, aquaculture planners, credit institutions and government agencies have  jointly evolved a partnership strategy by identifying the criteria for registration of these private extension service  providers, potential areas of collaboration, roles of various development institutions and a framework to concretize this  approach. This public-private partnership, a win-win approach would give a synergistic push for aquaculture extension  service and eventually lead to sustainable aquaculture in India.
Keywords: Aquaculture extension service; farmers' perception; public-private partnership; win-win strategy